Serum microRNA screening and functional studies reveal miR-483-5p as a potential driver of fibrosis in systemic sclerosis. (May 2018) - Chouri, Eleni; Servaas, Nila H.; Bekker, Cornelis P.J.; Affandi, Alsya J.; Cossu, Marta; Hillen, Maarten R.; Angiolilli, Chiara; Mertens, Jorre S.; van den Hoogen, Lucas L.; Silva-Cardoso, Sandra; van der Kroef, Maarten; Vazirpanah, Nadia; et al.
Abstract: Objective: MicroRNAs (miRNAs) are regulatory molecules, which have been addressed as potential biomarkers and therapeutic targets in rheumatic diseases. Here, we investigated the miRNA signature in the serum of systemic sclerosis (SSc) patients and we further assessed their expression in early stages of the disease. Methods: The levels of 758 miRNAs were evaluated in the serum of 26 SSc patients as compared to 9 healthy controls by using an Openarray platform. Three miRNAs were examined in an additional cohort of 107 SSc patients and 24 healthy donors by single qPCR. MiR-483-5p expression was further analysed in the serum of patients with localized scleroderma (LoS) (n = 22), systemic lupus erythematosus (SLE) (n = 33) and primary Sjögren's syndrome (pSS) (n = 23). The function of miR-483-5p was examined by transfecting miR-483-5p into primary human dermal fibroblasts and pulmonary endothelial cells. Results: 30 miRNAs were significantly increased in patients with SSc. Of these, miR-483-5p showed reproducibly higher levels in an independent SSc cohort and was also elevated in patients with preclinical-SSc symptoms (early SSc). Notably, miR-483-5p was not differentially expressed in patients with SLE or pSS, whereas it was up-regulated in LoS, indicating that this miRNA could be involved in the development of skin fibrosis. Consistently, miR-483-5p overexpression in fibroblasts and endothelial cells modulated the expression of fibrosis-related genes. Conclusions: Our findings showed that miR-483-5p is up-regulated in the serum of SSc patients, from the early stages of the disease onwards, and indicated its potential function as a fine regulator of fibrosis in SSc. Highlights: The profile of circulating miRNAs is markedly altered in the serum of SSc patients. miR-483-5p was found reproducibly up-regulated in two independent SSc cohorts. miR-483-5p upregulation was evident already in patients with early SSc symptoms. miR-483-5p was elevated in SSc and LoS, autoimmune diseases with fibrotic features. Functional studies revealed a potential role of miR-483-5p in fibrosis development.